Anmeldelser - Koldau, Linda Maria (Danish Yearbook of Musicology, 2010)
Review of: Ritus et Artes: Traditions and Transformations Vol. 1. Eyolf Østrem and Nils Holger Petersen: Medieval Ritual and Early Modern Music. The Devotional Practice of Lauda Singing in Late-Renaissance Italy. Turnhout: Brepols, 2008. Vol. 2. Sven Rune Havsteen, Nils Holger Petersen, Heinrich W. Schwab, and Eyolf .strem (eds.): Creations. Medieval Rituals, the Arts, and the Concept of Creation. Turnhout: Brepols, 2007. Vol. 3. Margrete Syrstad Andås, Øystein Ekroll, Andreas Haug, and Nils Holger Petersen (eds.): The Medieval Cathedral of Trondheim. Architectural and Ritual Constructions in their European Context. Turnhout: Brepols, 2007. Vol. 4. Mette B. Bruun and Stephanie Glaser (eds.): Negotiating Heritage. Memories of the Middle Ages. Turnhout: Brepols, 2009